Knowledge and Practices of Breast Self-Examination among Female Students of Bahria University of Health Sciences Karachi: Breast Self-Examination Knowledge and Practices - Tanwir, Farzeen; Razzaq, Abida; Ijaz, Bushra; Bibi, Tauqeer; Hafeez, Nabeel; Gulzada, Muhammad; Fahim, Muhammad Faisal (Pakistan Journal of Health Sciences, 2025)
Breast Self-Examination is an efficient approach for investigating physical and visual abnormalities in breast tissue. Objective: To evaluate the awareness, knowledge, practice of breast self-examination among female university students in five colleges of Bahria University Health Sciences Karachi. Methods: A cross-sectional study at Bahria University Health Sciences Campus Karachi with random sampling among female students from the Dental, Medical, Doctor of Physical Therapy, Nursing sections and Medical Laboratory Technicians. The data were collected using a self-administered google questionnaire form distributed online via WhatsApp. The questionnaire encompassed sections on the socio-demographic characteristics of the participants, as well as their awareness, knowledge, attitude, and practice towards BSE. For data analysis SPSS Software version 25.0 was used. Results: 240 female participants were enrolled in study, 77.5% knew the meaning of BSE, while 31.7% had complete knowledge. 5.4% BDS students did it in routine practice, 63% believed, it helps in cancer monitoring, 22.8% performed to detect nodules and 8.7% carried out because of family history. Out of 110 participants from nursing section, 7.3% followed BSE in routine practice, 65.5% believed it’s beneficial in the detection of cancer. However, the main reason for performing was detection of cancer 62.9%. Several barriers were encountered such as time constraint, lack of knowledge 46.7%, uncomfortable 6.7%, fear 30.4% and misconception. Conclusions: Participants had understanding of BSE but they lacked complete knowledge of breast self-examination due to limited access to health care resources and insufficient understanding about the technique also encounter significant barriers during practicing.